URGENSI PENANAMAN AQIDAH DALAM PENDIDIKAN ISLAM - Fitriana Rusyai Ali Ahmad (Universitas Muhammadiyah Tangerang, 2019)
Aqeedah is not just a belief that is in the hearts of men. But aqeedah is essentially a strong belief that is able to encourage a Muslim to want to do or do good deeds. If someone's true and lurius aqidah, then it will be true and straight also the path taken, and vice versa.Aqeedah is a major problem in the teachings of Islam. Because it involves the fundamental beliefs of all deeds. Muslims and non-Muslims can be distinguished from the side of amaliyah or his actions; whether reflecting Muslim's amaliyah or not. What is done is worth the good in the eyes of humans. Departing from this, the writer tries to actualize the urgency of planting aqidah in Islamic education. and behavior patterns based on pure Islamic aqeedah. Keywords: Urgency, Aqidah Cultivation, Islamic Education